ANALISIS RESEPSI FILM YUNI : FILM PERLAWANAN PEREMPUAN BANTEN TERHADAP KETIDAKADILAN GENDER - Rahma Aulia, Zulfa; Hasfi, Nurul; Sunarto, Sunarto (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
Film Yuni is a film that brings up the issue of women's resistance to patriarchal domination. This research uses qualitative methodology with Stuart Hall's reception analysis to determine the audience's meaning position based on dominant, negotiation and opposition positions. To reveal the dominant meaning that emerges, this research uses Roland Barthes' semiotics. The theory used in this research is Muted Group Theory. This research aims to determine the representation of Banten women's resistance to gender injustice in the Film Yuni and to determine the audience's reception regarding the issue of Banten women's resistance to gender injustice in the Film Yuni. The results of research related to the representation of Banten women's resistance to gender injustice in the film Yuni found that women resisted by expressing their desire to continue their education, rejecting early marriage proposals directly, filing for divorce, deciding to continue their education. having free sex, crying, living alone and independently, and escaping from early marriage. Regarding public reception, the research results show that the majority of informants are in an oppositional position regarding the silencing process and a dominant position in women's resistance strategies.Keywords : Film, Woman Resistance, Reception Analysis